Internalization of Pseudomonas aeruginosa Strain PAO1 into Epithelial Cells Is Promoted by Interaction of a T6SS Effector with the Microtubule Network. - Sana,TG; Baumann,C; Merdes,A; Soscia,C; Rattei,T; Hachani,A; Jones,C; Bennett,KL; Filloux,A; Superti-Furga,G; Voulhoux,R; Bleves,S (mBio, 2015)
Invasion of nonphagocytic cells through rearrangement of the actin cytoskeleton is a common immune evasion mechanism used by most intracellular bacteria. However, some pathogens modulate host microtubules as well by a still poorly understood mechanism. In this study, we aim at deciphering the mechanisms by which the opportunistic bacterial pathogen Pseudomonas aeruginosa invades nonphagocytic cells, although it is considered mainly an extracellular bacterium. Using confocal microscopy and immunofluorescence, we show that the evolved VgrG2b effector of P. aeruginosa strain PAO1 is delivered into epithelial cells by a type VI secretion system, called H2-T6SS, involving the VgrG2a component. An in vivo interactome of VgrG2b in host cells allows the identification of microtubule components, including the γ-tubulin ring complex (γTuRC), a multiprotein complex catalyzing microtubule nucleation, as the major host target of VgrG2b. This interaction promotes a microtubule-dependent internalization of the bacterium since colchicine and nocodazole, two microtubule-destabilizing drugs, prevent VgrG2b-mediated P. aeruginosa entry even if the invasion still requires actin. We further validate our findings by demonstrating that the type VI injection step can be bypassed by ectopic production of VgrG2b inside target cells prior to infection. Moreover, such uncoupling between VgrG2b injection and bacterial internalization also reveals that they constitute two independent steps. With VgrG2b, we provide the first example of a bacterial protein interacting with the γTuRC. Our study offers key insight into the mechanism of self-promoting invasion of P. aeruginosa into human cells via a directed and specific effector-host protein interaction. IMPORTANCE: Innate immunity and specifically professional phagocytic cells are key determinants in the ability of the host to control P. aeruginosa infection. However, among various virulence strategies, includi